IDENTIFIKASI FAKTOR KETERLAMBATAN PBG DAN SLF MELALUI SIMBG DI KOTA DENPASAR: Identification of Factors Causing PBG And SLF Delays Through SIMBG in Denpasar City - Putra, I Kadek Andrea; Indramanik, Ida Bagus Gede; Astariani, Ni Kadek; Wiradnyana, I Gede Oka (Ganec Swara, 2025)
This study aims to identify the factors causing delays in issuing Building Approval (PBG) and Certificate of Function Worthiness (SLF) through the Building Management Information System (SIMBG) in Denpasar City and determine the most dominant factor influencing the delay. A descriptive quantitative approach was employed by distributing questionnaires to 147 respondents. Data were analyzed using SPSS version 25 through validity, reliability, and descriptive tests. The results indicate that all indicators are valid (r count 0.465–0.625 > r table 0.159) and reliable (Cronbach’s Alpha 0.778–0.794). The main causes of delay include technological issues (mean score 4.42), limited facilities (3.98), ineffective time management (4.21), service quality and staff knowledge (4.15), complicated procedures (3.87), and relatively high costs (3.76). The most dominant factor is the frequent occurrence of system errors (score 4.56; 84.4%), which hampers the process until the system recovers. The study concludes that the success of PBG and SLF issuance depends not only on technology but also on infrastructure, human resource competence, and procedural efficiency. Recommendations include improving system stability, staff training, optimizing time management, and simplifying procedures to achieve more effective public services